The after hours : - Plath, David W. (University of California Press, 1969)
This is the first major work to deal with the question of leisure time in a modernized non-Western society and it is a significant contribution to this important area of knowledge. It is written in an exceptionally readable style and will appeal to both the specialist and non-specialist. Recommended for most collections.